Kinerja Keperawatan di Rumah Sakit Bhayangkara Pekanbaru - Nur Maimun; Afri Yelina (Jurnal Kesehatan Komunitas, 2016)
The assessment of performance is the process of judging the result of the work of personnel in a performance appraisal organization through an instrument. Give help in based on capability of being obtained through education, the motivation, work experience, and compensation also closely related to the performance of a person. The purpose of the research is to know the factors that associated the performance of nursing in hospital Bhayangkara Pekanbaru. Type of this research is quantitative analytic with Cross Sectional Study design. Population and sample is 58 people. The collection of data with conducted the questionaire, Analysis of data was performed using univariate and bivariate with statistical test Chi-Square. Result of the research the motivation OR = 18,333, the work experience OR = 9,896, the compensation performance of nursing staff OR = 13,33. Suggested to management Bhayangkara hoprital Pekanbaru can become the facilitator in improving the human resources ti get education and knowledge are higher, motivate exertion nursing, simulation training and that deatls with nursing, and noticed compensation.